Desain Didaktis Pada Materi Pecahan Dan Pengaruhnya Terhadap Kemampuan Problem Solving - Maula, Syahrul; Arisetyawan, Andika (Didaktika, 2022)
Problem Solving is important because it is expected to provide students with the ability to solve problems in theory or practice in everyday life, one of which is in learning mathematics because every human activity is always related to mathematics. This paper will discuss the effect of didactic design on fractional material on the problem solving abilities of students at SD Negeri Sepang for the 2021-2022 academic year. This is because the methods of learning mathematics in improving students' problem solving abilities are very diverse, one of which is the didactic method of mathematics. Based on this, this paper was made with the aim of knowing the effect of didactic design on fractional material on the problem solving abilities of elementary school students. The method used is quantitative with experimental techniques. A quasi-experimental design is analyzed using SPSS 21 for Windows. Based on the results of data analysis, it is known that after the learning method using the didactic design on fractional material was applied, students' problem solving abilities increased even though in the moderate category after applying the didactic design learning method on the fractional material. This can be seen from the increase in the average posttest result of the experimental class of 61.354 from the average of the experimental class's pretest result of 27.917. Meanwhile, the average N-gain score for the experimental class was 0.4641 which was categorized as moderate. The results of hypothesis testing with paired sample t test. The effect of didactic design on fractional material on students' problem solving abilities is that there is a significant effect because based on SPSS output, the Sig- (2-tailed) value is 0.000 0.05.